penelitian Water Pollution Index and Microplastic Ecological Risk in The North Coastal Area of Situbondo - Arisda Maryama Santikanuri; Riyanto Haribowo; Sri Wahyuni (Postgraduate, University of Mataram, 2025)
Microplastic pollution in rivers can harm ecosystems and water quality. This study aims to assess water quality and the ecological risk of microplastics in 15 locations in the North Coastal Area of Situbondo, which include rivers and estuaries. Water samples were analyzed based on water quality parameters, such as pH, TDS, ammonia, salinity, turbidity, DO, and BOD. Microplastics were identified using binocular microscopes and FTIR, with characteristics (size, shape, color) recorded. The Water Pollution Index (IP) showed a mild level of pollution with values ranging from 1.322 to 3.897, where IP values 1-3 are considered